Within‐patient comparison of His‐bundle pacing, right ventricular pacing, and right ventricular pacing avoidance algorithms in patients with PR prolongation: Acute hemodynamic study. (5th October 2020) - Keene, Daniel; Shun‐Shin, Matthew J.; Arnold, Ahran D.; March, Katherine; Qureshi, Norman; Ng, Fu Siong; Tanner, Mark; Linton, Nicholas; Lim, Phang B.; Lefroy, David; Kanagaratnam, Prapa; Peters, Nicholas S.; et al.
Abstract: Aims: A prolonged PR interval may adversely affect ventricular filling and, therefore, cardiac function. AV delay can be corrected using right ventricular pacing (RVP), but this induces ventricular dyssynchrony, itself harmful. Therefore, in intermittent heart block, pacing avoidance algorithms are often implemented. We tested His‐bundle pacing (HBP) as an alternative. Methods: Outpatients with a long PR interval (>200 ms) and intermittent need for ventricular pacing were recruited. We measured within‐patient differences in high‐precision hemodynamics between AV‐optimized RVP and HBP, as well as a pacing avoidance algorithm (Managed Ventricular Pacing [MVP]). Results: We recruited 18 patients. Mean left ventricular ejection fraction was 44.3 ± 9%. Mean intrinsic PR interval was 266 ± 42 ms and QRS duration was 123 ± 29 ms. RVP lengthened QRS duration (+54 ms, 95% CI 42–67 ms, p < .0001) while HBP delivered a shorter QRS duration than RVP (−56 ms, 95% CI −67 to −46 ms, p < .0001). HBP did not increase QRS duration (−2 ms, 95% CI −8 to 13 ms, p = .6). HBP improved acute systolic blood pressure by mean of 5.0 mmHg (95% CI 2.8–7.1 mmHg, p < .0001) compared to RVP and by 3.5 mmHg (95% CI 1.9–5.0 mmHg, p = .0002) compared to the pacing avoidance algorithm. There was no significant difference in hemodynamics between RVP and ventricular pacing avoidance ( p = .055). Conclusions: HBP provides better acute cardiac function than pacing avoidance algorithms and RVP, in patients with prolonged PR intervals. HBP allows normalization of prolonged AV delays (unlike pacing avoidance) and does not cause ventricular dyssynchrony (unlike RVP). Clinical trials may be justified to assess whether these acute improvements translate into longer term clinical benefits in patients with bradycardia indications for pacing.